Natural Orifice Specimen Extraction Surgery Colorectal Cancer (Springer Singapore, 2018)
This introduces the theoretical and practical guide of NOSES. The book introduced 10 different techniques of NOSES for colorectal neoplasms based on extensive high-quality surgical images. The first part mainly describes the development process of NOSES and the current achievements of these techniques which will provide readers a general understanding of NOSES. The second part elaborates on ten different surgical procedures specific to position of tumor location of NOSES in detail. All key technical points and operational skills regarding to NOSES are displayed by both high-quality images. The indications and contraindications are also strictly determined in this book. In addition to the elaboration of NOSES, each chapter of this book also conduct a detailed and comprehensive analysis the hot spots, technical difficulties and key issues with regard to laparoscopic surgery for colorectal cancer. This book is suitable for the colorectal cancer surgeons and doctors of general surgery.